Poda e raleio de frutos na produção e fenologia em pessegueiro ‘Suncrest’ - Silva, Fábio Oseias dos Reis (2015)
Branch pruning and fruit thinning are techniques commonly used in fruit-culture, remarkably the known temperate climate fruit trees. Those strategies aim to reduce the fruit bearing alternation and provide the maintenance or increase of fruit size in order to please the consumer. Within that context, it was intended through this work to evaluate both branch pruning and fruit thinning upon fruit yield and phenology in peach tree ‘suncrest’. In the first experiment, the influence of the intensity of branch pruning and fruit thinning upon the vegetative characteristics of the branches named rosette (branches of about 2 cm), medium branches (branches of up to 30 cm), vigorous branches (branches longer than 30 cm), carbohydrates yield in the plants and fruit yield was evaluated. It follows that strong pruning influences the increase of branches in terms of leaf characteristics above all on the vigorous branches. Pruning intensity does not influence the growth of the bearing branch up to 30 cm long and the rosette, in addition, it does not interfere in the content of the carbohydrates starch, fructose, glucose and sorbitol in the stem of plants. The more intense pruning, the greater the amount of vigorous branches and leaf area. Fruit thinning influences positively the starch content in the stem of plants. Medium pruning associated with fruit thinning favors the increase of sucrose in the stem of plants. Considering all the variables, the utilization of medium pruning and fruit thinning is recommended which provide increased yields and fruit mass, storing reserves for the following cycle. In the second experiment, the influence of branch pruning and fruit thinning upon the reproductive phenological behavior was evaluated, above all, the fruit set rate. It follows that branch pruning as well as fruit thinning influences the flowering period of peach trees. The different pruning and thinning intensities do not affect the fruit set rate, but they exert a strong influence during the growth and development of flowers and fruit. Medium pruning and fruit thinning provide a flowering period ideal for the studied conditions, though the choice of the ideal management type will depend upon the farmer’s objective.